2014
DOI: 10.1371/journal.pone.0094001
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Metabolomic Profiling Suggests Early Indications for Predisposition to Latent Insulin Resistance in Children Conceived by ICSI

Abstract: BackgroundThere have been increasing indications about an epigenetically-based elevated predisposition of assisted reproductive technology (ART) offspring to insulin resistance, which can lead to an unfavorable cardio-metabolic profile in adult life. However, the relevant long-term systematic molecular studies are limited, especially for the IntraCytoplasmic Sperm Injection (ICSI) method, introduced in 1992. In this study, we carefully defined a group of 42 prepubertal ICSI and 42 naturally conceived (NC) chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 48 publications
5
43
0
2
Order By: Relevance
“…Glucocorticoids are important mediators of obesity and insulin resistance, and disruption of the hypothalamic–pituitary–adrenal axis has been proposed as a mechanism for unfavorable metabolic outcomes after in vitro conception (Belva et al ., ). Interestingly, lower salivary and serum cortisol levels have been reported in ICSI‐conceived girls compared to SC girls, although these results were based on single measurements (Belva et al ., ; Gkourogianni et al ., ). Mean salivary cortisol in the Belgium cohort was lower in ICSI‐conceived girls, which remained after adjusting for current characteristics, and early life and maternal factors (Belva et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Glucocorticoids are important mediators of obesity and insulin resistance, and disruption of the hypothalamic–pituitary–adrenal axis has been proposed as a mechanism for unfavorable metabolic outcomes after in vitro conception (Belva et al ., ). Interestingly, lower salivary and serum cortisol levels have been reported in ICSI‐conceived girls compared to SC girls, although these results were based on single measurements (Belva et al ., ; Gkourogianni et al ., ). Mean salivary cortisol in the Belgium cohort was lower in ICSI‐conceived girls, which remained after adjusting for current characteristics, and early life and maternal factors (Belva et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Mean salivary cortisol in the Belgium cohort was lower in ICSI‐conceived girls, which remained after adjusting for current characteristics, and early life and maternal factors (Belva et al ., ). In a smaller cohort, an extensive review of plasma metabolomics also revealed lower cortisol levels in a subgroup of ICSI‐conceived girls aged 4 to 9 years compared to SC girls, alongside significant differences in 36 metabolites indicating early insulin resistance in the ICSI group (Gkourogianni et al ., ). Another unexpected finding in this latter study was lower inflammatory markers in the ICSI group compared to SC controls including YKL‐40, which normally represents a marker of inflammation, obesity, and insulin resistance (Gkourogianni et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Metabolomics analyses in children have found that higher circulating branched chain amino acids (BCAAs) are associated with obesity status (10, 11), as well as subclinical risk factors for metabolic disease like insulin resistance (10, 12). Studies in adults have shown that elevations in serum branched chain amino acids (BCAAs) are detectable several years prior to development of insulin resistance and incident type 2 diabetes (13, 14), even among individuals of similar weight status (13).…”
Section: Introductionmentioning
confidence: 99%
“…In another study by Chen et al [48] peripheral insulin sensitivity as measured by the hyperinsulinemic-euglycemic clamp was significantly lower in IVF vs. naturally conceived young adults. Gkourogianni et al [49] performed a metabolomic analysis on girls conceived by ICSI and revealed significantly increased levels on most metabolites related to obesity, insulin resistance and metabolic syndrome, compared to controls, even before they were biochemically evident.…”
Section: Sakka and Ioannis Papassotiriou)mentioning
confidence: 99%